Targeting mitochondrial respiration and the BCL2 family in high‐grade MYC‐associated B‐cell lymphoma - Donati, Giulio; Ravà, Micol; Filipuzzi, Marco; Nicoli, Paola; Cassina, Laura; Verrecchia, Alessandro; Doni, Mirko; Rodighiero, Simona; Parodi, Federica; Boletta, Alessandra; Vellano, Christopher P.; Marszalek, Joseph R.; et al. (Molecular oncology, 2022)
Multiple molecular features, such as activation of specific oncogenes (e.g., MYC, BCL2) or a variety of gene expression signatures, have been associated with disease course in diffuse large B‐cell lymphoma (DLBCL), although their relationships and implications for targeted therapy remain to be fully unraveled. We report that MYC activity is closely correlated with—and most likely a driver of—gene signatures related to oxidative phosphorylation (OxPhos) in DLBCL, pointing to OxPhos enzymes, in particular mitochondrial electron transport chain (ETC) complexes, as possible therapeutic targets in high‐grade MYC‐associated lymphomas. In our experiments, indeed, MYC sensitized B cells to the ETC complex I inhibitor IACS‐010759. Mechanistically, IACS‐010759 triggered the integrated stress response (ISR) pathway, driven by the transcription factors ATF4 and CHOP, which engaged the intrinsic apoptosis pathway and lowered the apoptotic threshold in MYC‐overexpressing cells. In line with these findings, the BCL2‐inhibitory compound venetoclax synergized with IACS‐010759 against double‐hit lymphoma (DHL), a high‐grade malignancy with concurrent activation of MYC and BCL2. In BCL2‐negative lymphoma cells, instead, killing by IACS‐010759 was potentiated by the Mcl‐1 inhibitor S63845. Thus, combining an OxPhos inhibitor with select BH3‐mimetic drugs provides a novel therapeutic principle against aggressive, MYC‐associated DLBCL variants. We show that MYC activity is closely correlated with OxPhos‐associated gene signatures in human B‐cell lymphomas and sensitizes B cells to the mitochondrial complex I inhibitor IACS‐010759. This molecule shows synergy with select BH3‐mimetic drugs in killing cancer cells, and in particular with the BCL2 inhibitor venetoclax against the aggressive double‐hit lymphoma subtype, with promising antitumoral effects in preclinical models.